2016
DOI: 10.13189/ujph.2016.040502
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Socioeconomic Factors on Tuberculosis Prevalence in Latvia

Abstract: Tuberculosis (TB) is commonly linked to poverty, overcrowding and malnutrition. It was known earlier that TB more frequently attacks the most vulnerable part of the society-people who have lower socioeconomic status and harmful habits. Being aware of determinants of TB, attenuation of morbidity can be accomplished. This paper identifies impact of socioeconomic risk factors and risk conditions on prevalence of TB in Latvia, using the Four Layers of Health Determinants Model. The impact of risk factors and risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…From 2013 to 2016, the situation improved again, with registered new TB cases declining from 38.1 per 100 000 in 2013 to 28.4 in 2016 [ 5 ]. However, vulnerable and socially marginalized individuals are disproportionately affected [ 6 ]. Despite a high treatment success rate (88%) among new drug-susceptible TB patients, factors influencing unsuccessful treatment outcomes in vulnerable individuals including unemployment, alcohol and drug use, and HIV are consistently reported in epidemiological studies on TB and drug-resistant (DR) TB in the Baltic States [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…From 2013 to 2016, the situation improved again, with registered new TB cases declining from 38.1 per 100 000 in 2013 to 28.4 in 2016 [ 5 ]. However, vulnerable and socially marginalized individuals are disproportionately affected [ 6 ]. Despite a high treatment success rate (88%) among new drug-susceptible TB patients, factors influencing unsuccessful treatment outcomes in vulnerable individuals including unemployment, alcohol and drug use, and HIV are consistently reported in epidemiological studies on TB and drug-resistant (DR) TB in the Baltic States [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini berbeda dengan penelitian Ivanovs dkk yang menyatakan bahwa seseorang yang tidak bekerja memiliki risiko 6,6 kali lebih tinggi untuk terkena TB dibandingkan dengan seseorang yang berkerja. 10 Pada penelitian ini didapatkan bahwa tidak terdapat hubungan antara penerapan etika batuk pada penderita TB Paru dengan kejadian TB Paru pada pasangan di kecamatan Darul Imarah Kabupaten Aceh Besar. Hal ini tidak dapat diambil kesimpulan diakibatkan oleh sangat rendahnya kejadian pada pasangan.…”
Section: Pembahasanunclassified
“…Previous ecological studies have found links between high TB rates in different areas and low levels of education, high levels of poverty, and income inequality [ 5 7 ]. In individual-level studies, authors determined economic deprivation, homelessness, prison terms, injection of drugs, HIV/AIDS, and migration from high TB-rate countries as risk factors for TB [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%